Fostering ICT Competencies in Blended Learning: Role of Curriculum Content, Material, and Teaching Strategies - Ashraf, Muhammad Azeem; Iqbal, Javed; Arif, Muhammad Irfan; Asghar, Muhammad Zaheer (Frontiers in Psychology, 2022)
The study examined the direct and indirect influence of ICT integrated curriculum content, material, and teaching strategies on ICT competencies of students in blended learning. The ICT integrated teaching strategies were used as a mediator in between the relationships of curriculum content, material and ICT competencies. We used a survey questionnaire containing 26 items on the variables of research in this study. The data were collected from six universities in the Hunan province of China. The Target population consisted of undergraduate students of blended learning. In total, 486 participants participated in the study. PLS-SEM (partial least squares-structural equation modeling) was applied to measure the relationships among variables. The results revealed that there were significant and positive relationships among ICT integrated curriculum content, material, teaching strategies and ICT competencies of students. Further, it was also revealed that ICT integrated teaching strategies in blended learning mediated the relationships in between ICT integrated curriculum content, material and ICT competencies. It was concluded that effective curriculum content, curriculum material and teaching strategies are the critical predictors of ICT competencies. Moreover, teaching strategies worked as an intervening factor between curriculum content, curriculum material and ICT competencies. The practical implications and directions for future research are also presented in this study..